Vaccines, Politics and Mandates: Can We See the Forest for the Trees?; Comment on "Convergence on Coercion: Functional and Political Pressures as Drivers of Global Childhood Vaccine Mandates" - Noni E. MacDonald; Ève Dubé; Jeannette Comeau (Kerman University of Medical Sciences, 2023)
Under-vaccination is a complex problem that is not simple to address whether this is for routine childhood immunization or for coronavirus disease 2019 (COVID-19) vaccination. Vaccination mandates has been one policy instrument used to try to increase vaccine uptake. While the concept may appear straight forward there is no standard approach. The decision to shift to a more coercive mandated program may be influenced by both functional and/or political needs. With mandates there may be patient and/or public push back. Anti-mandate protests and increased public polarization has been seen with COVID-19 vaccine mandates. This may negatively impact on vaccine acceptance ie, be counterproductive, causing more harm than overall good in the longer term. We need a better understanding of the political and functional needs that drive policy change towards mandates as well as cases studies of the shorter- and longer-term outcomes of mandates in both routine and pandemic settings.